Displaced retinal ganglion cells in albino and pigmented rats - Nadal-Nicolás, Francisco M.; Salinas-Navarro, Manuel; Jiménez-López, Manuel; Sobrado-Calvo, Paloma; Villegas-Pérez, María P.; Vidal-Sanz, Manuel; Agudo-Barriuso, Marta (Frontiers in Neuroanatomy, 2014)
We have studied in parallel the population of displaced retinal ganglion cells (dRGCs) and normally placed (orthotopic RGCs, oRGCs) in albino and pigmented rats. Using retrograde tracing from the optic nerve, from both superior colliculi (SC) or from the ipsilateral SC in conjunction with Brn3 and melanopsin immunodetection, we report for the first time their total number and topography as well as the number and distribution of those dRGCs and oRGCs that project ipsi- or contralaterally and/or that express any of the three Brn3 isoforms or melanopsin. The total number of RGCs (oRGCs+dRGCs) is 84,706±1,249 in albino and 90,440±2,236 in pigmented, out of which 2,383 and 2,428 are melanopsin positive (m-RGCs), respectively. Regarding dRGCs: i/ albino rats have a significantly lower number of dRGCs than pigmented animals (0.5% of the total number of RGCs vs. 2.5%, respectively), ii/ dRGCs project massively to the contralateral SC, iii/ the percentage of ipsilaterality is higher for dRGCs than for oRGCs, iv/ a higher proportion of ipsilateral dRGCs is observed in albino than pigmented animals, v/ dRGC topography is very specific, they predominate in the equatorial temporal retina, being densest where the oRGCs are densest, vi/ Brn3a detects all dRGCs except half of the ipsilateral ones and those that express melanopsin, vii/ the proportion of dRGCs that express Brn3b or Brn3c is slightly lower than in the oRGC population, viii/ a higher percentage of dRGCs (13% albino, 9% pigmented) than oRGCs (2.6%) express melanopsin, ix/ few m-RGCs (displaced and orthotopic) project to the ipsilateral SC, x/ the topography of m-dRGCs does not resemble the general distribution of dRGCs, xi/ The soma size in m-oRGCs ranges from 10 to 21 µm and in m-dRGCs from 8 to 15 µm, xii/ oRGCs and dRGCs have the same susceptibility to axonal injury and hypertension. Although the role of mammalian dRGCs remains to be determined, our data suggest that they are not misplaced by an ontogenic mistake.